Leadership in a VUCA world - Sabina, Lou L.; Colwell, Christopher; Tager, James (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2023)
"COVID-19 ravaged the United States and the rest of the world in a similar manner as a Category V hurricane would, leaving no one safe in its wake. Unlike a hurricane though, where appropriate provisions and supports are possible and past experiences can help to prepare, how do you prepare for something Volatile, Uncertain, Complex, and Ambiguous such as a worldwide pandemic? Imagine having your high school graduation and prom ripped away from you with little to no warning. Imagine being a 40+ year professor and being told that "you are now going to teach hybrid with some students in the class and some students online," or imagine that you were accepted into the 2nd most prestigious Ph.D. program in the United States and dream of being a professor and look for those face-to-face mentoring opportunities on campus. This book addresses the lived experiences of many throughout the onset, duration, and the after-effects of the COVID-19 pandemic, and helps prepare readers for the never ending storm ahead. Our book offers guidance from leaders from different walks of life. We visit with a pastor who had to "get creative" to combat the pandemic, examine how school board members have interacted with parents and other community stakeholders, hear from a current superintendent in a large school district in Maine, and other stakeholders impacted by COVID-19. Our message is cautious, yet optimistic, to prepare the reader for life in a VUCA world"--